Model Soil Water Assessment Tool (SWAT) Untuk Prediksi Laju Erosi Dan Sedimentasi Sub Das Keduang Kabupaten Wonogiri - Nugroho, Prima; , Drs. Yuli Priyana, M.Si; , Sigit Haryadi, S.Hut., M.Eng. M.Sc (2015)
Erosion and sedimentation are the problems that often occur in the watershed ecosystem. Those problems can be reduced by applying a proper watershed management, especially in the upstream watershed. In this case, the model can be used to know the output of the performance of a watershed. Soil Water Assessment Tool (SWAT) is a hydrological model used to determine the impact of the land use and physical environmental conditions on the rate of erosion and sedimentation spatially and temporally. Keduang sub watershed is one of sub watersheds in Bengawan Solo river in which the upper course is located at Gajah Mungkur Reservoir. This research aims to: (1) know the spatial distribution hydrologic response unit (HRU) in the areas of research (2) know the accuracy of the SWAT in predicting the rate of erosion and sedimentation, (3) analyze the rate of erosion and sedimentation in Keduang sub watershed. The statistical method used to test the model is by using the equation Nash-Sutcliffe efficiency (NS) and the coefficient of determination. The results obtained is the distribution of HRU dominated by HRU fields with patterns clustered at the center and spread to the southern part, the results of model validation is R2 = 0.79 and NS = 0.41, which means the model can acceptable if the value of R2> 0.5, the area with a high erosion rate is 17,950.75 ha / 51.22% and 7,771.25 ha / 22.17% to a very high erosion rate, and the average sedimentation in Keduang sub watershed outlet of which 408.19 tons ha-1 yr-1 in 2011-2014.